Site-directed Spin Labeling and Electron Paramagnetic Resonance Determination of Vimentin Head Domain Structure - Aziz, Atya (American Society for Biochemistry and Molecular Biology, 2010)
Intermediate filament (IF) proteins have been predicted to have a conserved tripartite domain structure consisting of a largely α-helical central rod domain, flanked by head and tail domains. However, crystal structures have not been reported for any IF or IF protein. Although progress has been made in determining central rod domain structure, no structural data have been reported for either the head or tail domains. We used site-directed spin labeling and electron paramagnetic resonance to analyze 45 different spin labeled mutants spanning the head domain of vimentin. The data, combined with results from a previous study, provide strong evidence that the polypeptide backbones of the head domains form a symmetric dimer of closely apposed backbones that fold back onto the rod domain, imparting an asymmetry to the dimer. By following the behavior of spin labels during the process of in vitro assembly, we show that head domain structure is dynamic, changing as a result of filament assembly. Finally, because the vimentin head domain is the major site of the phosphorylation that induces disassembly at mitosis, we studied the effects of phosphorylation on head domain structure and demonstrate that phosphorylation drives specific head domain regions apart. These data provide the first evidence-based model of IF head domain structure.